TEACHING LISTENING AND READING SKILLS EFFECTIVELY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores effective methods for teaching listening and reading skills to technical college students. Listening and reading are fundamental language skills that enhance comprehension, vocabulary acquisition, and communication competence. The article examines common challenges faced by students, including difficulties in understanding spoken English and reading authentic texts. Practical strategies for teaching listening and reading are discussed, such as pre-listening/pre-reading activities, extensive and intensive practice, use of authentic materials, and integration of technology. The findings suggest that structured approaches and interactive methods significantly improve students’ listening and reading proficiency, contributing to overall language development and academic success.